Corticosteroids for the prevention of bronchopulmonary dysplasia in preterm infants: an overview of Cochrane reviews. Issue 6 (November 2013) - Harrold, J.; Ali, S.; Oleszczuk, M.; Lacaze‐Masmonteil, T.; Hartling, L.
Abstract Background Bronchopulmonary dysplasia (BPD) is an important complication associated with considerable morbidity in preterm infants. Corticosteroids in various regimens have been tried out to prevent BPD. Objective To examine the evidence from Cochrane systematic reviews regarding the effectiveness and associated complications of corticosteroids used to prevent BPD in preterm infants. Methods The Cochrane Database of Systematic Reviews was searched to identify reviews of corticosteroids for BPD in preterm infants. Data were extracted by one investigator, and checked by a second investigator for accuracy. Results are presented as risk ratios (RR) with 95% confidence intervals (CI). We considered <8 days as early and >7 days as late administration. Main results Six reviews (67 trials and 6535 patients) were included and covered three main comparisons: inhaled corticosteroids versus placebo, inhaled versus systemic corticosteroids and systemic corticosteroids versus placebo. Systemic corticosteroids compared with placebo significantly reduced the incidence of BPD (early: RR 0.79, 95% CI 0.71–0.88; late: RR 0.72, 95% CI 0.63–0.82), and BPD or mortality (early: RR 0.89, 95% CI 0.84–0.95; late: RR 0.72, 95% CI 0.63–0.82) at 36 weeks post‐menstrual age. Similar results were observed for these outcomes assessed at 28 days of life at which time there was additionally a reduction in mortality (late: RR 0.49, 95% CI 0.28–0.85). There was a higher incidence of cerebral palsy associated with systemic corticosteroids compared with placebo when initiated early (RR 1.45, 95% CI 1.06–1.98). No differences in neurodisability based on Bayley Mental or Psychomotor Developmental Index scores were observed for inhaled or systemic corticosteroids compared with placebo. Hypertension was significantly increased in association with systemic corticosteroids versus placebo (early: RR 1.85, 95% CI 1.55–2.22; late: RR 2.66, 95% CI 1.58–4.49) as were gastrointestinal (GI) perforations when treatment was initiated early (RR 1.81, 95% CI 1.33–2.48). Author's Conclusion Systemic corticosteroids decrease BPD and early mortality in premature infants but have a risk of complications, particularly when initiated in the first week of life. Owing to the wide range of dosing protocols, timing of initiation, doses and duration of therapy in the included reviews, it is difficult to determine, based on the evidence examined in this overview, a protocol that is both safe and effective. Further research should focus on determining the most effective dose and timing of corticosteroid administration beyond the first week of life to maximize benefit in decreasing BPD and mortality while avoiding short‐ and long‐term harms.